Дидактична гра як засіб формування професійних ціннісних орієнтацій майбутнього фахівця-юриста - Мурзіна, Олена Анатоліївна (ЗНУ, 2012)
The article outlines the role of didactic play in shaping the future orientations of professional tsinnistnyh legal professionals. In the studies we have come to the conclusion that the didactic game is active means forming tsinnistnyh orientations of future legal professionals
Keywords: цінності; ціннісні орієнтації; професійно-ціннісні орієнтації; дидактична гра